Retreatment of a case with combined complex bone atrophy together with peri-implantitis. Importance of the reversibility of implant treatments - Anitua, Eduardo (2020)
Dental implants are an alternative treatment for extended the resolution of cases of edentulism. Since its inception in the year 70 have been a growing alternative to rehabilitate patients, especially in cases where conventional rehabilitations were not possible. Every time, in the dental office were more often we re-treatments of implants and cases with more complex atrophies. In the following case we show a re-treatment of failed implants attached to a situation of extreme atrophy combined vertical and horizontal. In cases of severe maxillary and mandibular atrophy, the use of short implants can shorten treatment times and simplify surgical techniques without sacrificing predictability as in the case shown.